Investigation of palladium cross-coupling reaction on verdazyl radicals - Petunin P. V. Pavel Vasilievich; Martynko E. А. Ekaterina Andreevna; Postnikov P. S. Pavel Sergeevich; Trusova M. E. Marina Evgenievna; Mostovich E. А. Evgeny Alekseevich (2017, 2017)
Title screen